PENERAPAN MODEL COOPERATIVE LEARNING TIPE JIGSAW DENGAN MEDIA GAMBAR UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR PADA PEMBELAJARAN MATEMATIKA SISWA KELAS IV SDN 2 NAMBAHREJO - Rusmartini Rusmartini (UNIVERSITAS MUHAMMADIYAH METRO, 2015)
The aims of this research were to increase the activities and the result of study by implementation of cooperative learning model type jigsaw with picture media. The method of the research was Classroom Action Reserach. The instrument of data collection used observation sheet and test. Technique of data analysis used qualitative and quantitative analysis. The result showed that the student activity in cycle I 62,58% (active) and cycle II 81,50%(activeenough). The result study of the cognitivie in cycle I 71,31%(good) and cycle II80,42%(good).